Pengaruh Kualitas Pelayanan dan Imersif Terhadap Kepuasan Pengunjung Bes Cinema di Kota Pangkalpinang - Junita, Dwi; Rizaldi, Zuhdi; Ramadhon, Faturrahman; Noviyanti , Indah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
In the midst of increasingly fierce competition, cinemas are required not only to show the latest films but also to provide a comfortable and satisfying viewing experience. The quality of service and immersive experiences in the entertainment world today are considered important elements that greatly influence visitors' understanding and experience. This research aims to determine the effect of service quality and immersive experiences on the satisfaction of visitors to BES Cinema in Pangkalpinang City. This study uses a quantitative approach by conducting surveys on a number of people who have visited BES Cinema. The collected data were analyzed using multiple linear regression to find out the extent of the influence of independent variabels, namely service quality and immersive experience, on the dependent variabel, which is the level of visitor satisfaction. Data collection was carried out using questionnaires. Research findings show that satisfying services and an atmosphere that supports the watching experience positively and significantly affect visitor satisfaction. This indicates that improvements in visual design and service aspects are crucial to maintaining visitor loyalty in the local cinema industry, as a comfortable atmosphere can enhance the overall quality of the experience. Thus, enhancements in service quality and immersive experiences can boost visitor satisfaction at BES Cinema in Pangkalpinang City.